Late Paleozoic deformation and exhumation in the Sierras Pampeanas (Argentina): 40Ar/39Ar-feldspar dating constraints - Löbens, Stefan (2017)
Systematic 40Ar/39Ar feldspar data obtained from the Sierras Pampeanas are presented, filling the gap between available high- (>~300 °C) and low-temperature (<~150 °C) thermochronological data. Results show Silurian–Devonian exhumation related to the late stages of the Famatinian/Ocloyic Orogeny for the Sierra de Pocho and the Sierra de Pie de Palo regions, whereas the Sierras de San Luis and the Sierra de Comechingones regions record exhumation during the Carboniferous. Comparison between new and available data points to a Carboniferous tectonic event in the Sierras Pampeanas, which represents a key period to constrain the early evolution of the proto-Andean margin of Gondwana. This event was probably transtensional and played a major role during the evolution of the Paganzo Basin as well as during the emplacement of alkaline magmatism in the retroarc.